Endoscopic transpapillary interventions in the diagnosis and treatment of biliary complications in patients after orthotopic liver transplantation - M. Sh. Khubutia; A. V. Chzhao; E. A. Soldatov; T. P. Pinchuk; A. N. Lotov; E. Yu. Pavlikova; K. I. Alekseyev (Трансплантология (Москва))
Objective: to evaluate the efficiency of endoscopic transpapillary interventions in the diagnosis and treatment of biliary complications in patients after orthotopic liver transplantation (OLT).Materials and methods. One hundred and seventy-one OLTs were carried out at the N.V. Sklifosovsky Research Institute of Emergency Care in January to October 2010. Of them, endoscopic transpapillary interventions into the bile ducts for biliary complications were undertaken in 13 (7.6%) patients. These patients underwent a total of 33 endoscopic retrograde cholangiographies (ERCG), 13 endoscopic papillosphincterotomies, 5 bouginages, and 22 stentings.Results. There were no fatal outcomes associated with endoscopic interventions. By and large, the immediate result of endoscopic treatment was positive in 10 (77.0%) patients. Our results of endoscopic treatment were comparable with the data available in the literature.Conclusion. ERCG can reveal post-OLT bile-biliary anastomostic strictures and failure, which serve as an indication for endoscopic bilioduodenal stenting with stepwise restenting.